Consequences of M&A team composition for deal outcomes: An inductive study - Paumen, Timo; Kroon, David; Khapova, Svetlana N. (Frontiers in Psychology, 2022)
While Merger & Acquisition (M&A) activity has reached unprecedented levels over recent years, M&A failure rates remain high. In explaining these disappointing outcomes, previous studies barely focused on the teams that manage these M&A transactions. Furthermore, only scant information exists on team members’ roles and skill sets. With an aim to contribute to filling this gap, we inductively explore a composition logic of M&A teams and its consequences for M&A outcomes by following a grounded theory approach and conducting semi-structured interviews with thirty M&A professionals. We identify three prevailing team roles (project manager, expert and executor) which require a specific set of soft and hard skills that explain how M&A teams can enable M&A success in terms of deal execution and completion. Furthermore, we provide evidence to how aspects of project timing, such as deadlines and simultaneous projects, shape the team members’ work. Finally, our findings underline the importance of accumulating experience and learning effects on M&A deal outcomes, shaping both M&A team culture and the team members’ skill sets.